VD_FINDINFO AP / 2010 / 68 vom 5. September 2008 - VD Tribunal cantonal (2008)
BAIL À LOYER, LOCAL PROFESSIONNEL, DÉFAUT DE LA CHOSE, DOMMAGES-INTÉRÊTS | 259a al. 1 CO, 262 CO, 451 ch. 2 CPC, 452 al. 2 CPC, 13 LTB